Revision of New World Leptocera Olivier (Diptera, Sphaeroceridae) - Buck, Matthias; Marshall, Stephen A. (Zootaxa, 2009)
The 35 species of Leptocera in the New World are revised and keyed. Five species groups are recognised: L. caenosa group (15 spp.: widespread), L. fontinalis group (10 spp.: North and Central America), L. fulva group (5 spp.: Florida and Neotropical), L. nigra group (1 sp.: Venezuela, introduced), L. plax group (3 spp.: Central America and Ecuador), species incertae sedis (L. schlingeri Richards: Ecuador, Peru). Twenty-one species are newly described (authorship by M.B.): L. argentinica sp.n., L. erratica sp.n., L. gongylotheca sp.n., L. longilimbata sp.n., L. papallacta sp.n., L. parallelipennis sp.n., and L. sphaerotheca sp.n. (L. caenosa group); L. angulispina sp.n., L. cymatonota sp.n., L. hexadike sp.n., L. kanata sp.n., L. neofinalis sp.n., L. neovomerata sp.n., and L. tenuispina sp.n. (L. fontinalis group); L. dicrofulva sp.n., L. insularum sp.n., L. prolixofulva sp.n., and L. rhadinofulva sp.n. (L. fulva group); L. plax sp.n., L. posteronitens sp.n., and L. tapanti sp.n. (L. plax group). Leptocera pararoralis Duda is given new status as subspecies of L. erythrocera Becker. Lectotypes are designated for L. aequilimbata Duda, L. pararoralis Duda, L. abdominiseta Duda and L. scutellaris (Williston) [= L. discalis (Malloch)]. The relationship between Leptocera and its putative sister genus Rachispoda is discussed in detail. Based on a newly hypothesized transformation series of the male cercus, Leptocera is probably paraphyletic with regard to Rachispoda. Putative synapomorphies for the different species groups of Leptocera are discussed and monophyly is demonstrated for all groups except the L. fontinalis group.